Generating Function Associated with the Product of Gegenbauer Polynomials - N.U. Khan; M. Kamarujjama; T. Kashmin (International Journal of Mathematics And its Applications, 2018)
This paper deals with general expansions which gives as special cases involving Legendre, Ultraspherical, and Tchebcheff polynomials, Appell, Bessel's and generalized hypergeometric functions of mathematical physics. The results extended Pathan and Kamarujjama expansion [7], Exton's generating function [5] and Feldheim's expansion [3]. A number of known and new generating functions are shown to follow as an application of the main result.